Comprehensive Functional Assessment of the Elderly in Institutions, Particularly in Terms of Social Life - Ojika, Kosei; Yamamoto, Toshiyuki; Yoshida, Tatsuya; Inagaki, Aki; Hashizume, Yoshio; Inagaki, Toshiaki; Niimi, Tatsuji (Nihon Rōnen Igakkai zasshi, 1993)
The purpose of this study was to clarify aspects of social life in a comprehensive functional assessment of 160 elderly subjects, over 60 years of age, in institutions for the elderly. Five items were assessed: economic conditions, marrital status, family conditions, family relationships and group behavior. The institutions were of 4 types: a geriatric hospital, a special nursing home for the aged, a home for the elderly and a home with moderate fees. The assessment of social life demonstrated significant correlation between the revised version of Hasegawa's Dementia Scale, activity of daily living and physical conditions. Inter-institution comparisons revealed significant differences in terms of economic conditions for the home for the elderly, family conditions for the home with moderate fees, and family relationships and group behavior for the geriatric hospital. Total grades across the 5 items were significantly lower for the geriatric hospital cases. This assessment proved useful to illuminate aspects of social life of the elderly in institutions.